Está en la página 1de 2

Cálculo Integral

Tarea

𝑑𝑦 2 𝑑𝑦 𝑑𝑦 2
1−( ) −2 1−( ) 𝑑𝑦 𝑑𝑦 𝑑𝑦
𝑑𝑥 𝑑𝑥 𝑑𝑥
𝑦= +( ) ln (1 + ) − 𝑥 [1 + (1 + ) ln⁡(1 + )]
4 2 𝑑𝑥 𝑑𝑥 𝑑𝑥
[ ]

𝑑𝑦
𝑅𝑒𝑚𝑝𝑙𝑎𝑧𝑎𝑚𝑜𝑠⁡ =𝑃
𝑑𝑥

1 − 𝑃2 − 2𝑃 1 − (𝑃)2
𝑦=[ ]+( [−1 − (1 + 𝑃)ln⁡(1 + 𝑃)] … (1)
) ln(1 + 𝑃) + 𝑥 ⏟
⏟ 4 2
𝑓
𝑔

𝑑𝑓 𝑑𝑔
𝑑𝑥 𝑥
= 𝑑𝑃 + 𝑑𝑃 … (2)
𝑑𝑃 𝑃 − 𝑓 𝑃 − 𝑓

𝑑𝑓
= − ln(𝑃 + 1) − 1 … (3)
𝑑𝑃

𝑑𝑔 𝑃 1 1−𝑃
= − − − 𝑃 ln(1 + 𝑃) + = −𝑃 − 𝑃 ln(1 + 𝑃) … (4)
𝑑𝑃 2 2 2

𝑃 − 𝑓 = 𝑃 + 1 + (1 + 𝑃)ln⁡(1 + 𝑃)

(4) y (3) en (2)

𝑑𝑥 𝑥(− ln(𝑃 + 1) − 1) −𝑃(1 + ln(1 + 𝑃))


= +
𝑑𝑃 𝑃 + 1 + (1 + 𝑃)ln⁡(1 + 𝑃) 𝑃 + 1 + (1 + 𝑃)ln⁡(1 + 𝑃)

𝑑𝑥 −𝑥 −𝑃
= +
𝑑𝑃 𝑃 + 1 𝑃 + 1

𝑑𝑥 1 −𝑃
+𝑥 = ⁡𝐸. 𝐷. 𝐿
𝑑𝑃 ⏟
𝑃+1 ⏟ 𝑃+1
𝐹 𝐺

1
𝑢 = 𝑒 ∫𝑃+1𝑑𝑃 = 𝑃 + 1

𝑑𝑥 1 −𝑃
𝑢 + 𝑢𝑥 =𝑢
𝑑𝑃 𝑃+1 𝑃+1

𝑥𝑢 = ∫ 𝑢𝐺𝑑𝑃

𝑃2
𝑥(𝑃 + 1) = − ∫ 𝑃𝑑𝑃 = − +𝐶
2

2𝐶 − 𝑃2
𝑥= … (5)
2(𝑃 + 1)
Reemplazamos (5) en (1)

1 − 𝑃2 − 2𝑃 1 − (𝑃)2 (2𝐶 − 𝑃2 )
𝑦=[ ]+( ) ln(1 + 𝑃) − [+1 + (1 + 𝑃)ln⁡(1 + 𝑃)]
4 2 2(𝑃 + 1)

1 − 𝑃2 − 2𝑃 1 − (𝑃)2 (2𝐶 − 𝑃2 ) (2𝐶 − 𝑃2 )


𝑦=[ ]+( ) ln(1 + 𝑃) − − ln⁡(1 + 𝑃)
4 2 2(𝑃 + 1) 2
𝑆. 𝐺⁡𝑑𝑒⁡𝐿𝑎𝑔𝑟𝑎𝑛𝑔𝑒
2𝐶 − 𝑃2
𝑥=
{ 2(𝑃 + 1)